An investigation of type 2 diabetes self-management in Taiwan - Wu, Hsiu-Li (2009)
In Taiwan, as in other countries, type 2 diabetes is a major public health problem. Taiwanese nurses are being called upon to play an increasingly large role in diabetes care, but little is known about the factors that contribute to good or poor diabetes self-management in the Taiwanese context.